The Role of Entrepreneurship Orientation and Competitive Strategies Toward Business Performance - Putri Tresnawati; Popy Rufaidah (Journal of International Conference Proceedings (JICP), 2018)
This study aims to investigate the effect of entrepreneurship orientation and competitive strategies on the business performance of Small and Medium Enterprises (SMEs) in the Foods and Beverages Sectors in West Java, Indonesia. The study adopted the following concepts to achieve the aims of the study: (1) Entrepreneurial orientation is a process that is attached to an entrepreneur in carrying out his business operations in the form of a proactive attitude in capturing business opportunities, innovation in producing products and services, and the courage to take risks in decision making (Weerawerdeena, 2003: 410); (2) Competitive strategies are a number of tactical steps to maintain a business so that it has better competitiveness than its competitors through the application of cost leadership, differentiation and focus strategies (Porter 1979); and (3) Business performance is the level of business success in achieving its goals through measurable indicators such as sales growth, capital growth, market growth, and profit growth (Munizu 2010). The study is executed to 120 business owners of the SMEs as the respondents of the study. The data analysis technique applied is Structural Equation Modeling (SEM) which is operated through LISREL program. The findings of the study show that the entrepreneurship orientation and competitive strategies simultaneously influenced toward the business performance of SMEs. Keywords: entrepreneurship orientation, competitive strategy, business performance, SME, West Java